Implementation of Missouri Mathematics Project Learning Model on Mathematical Learning Achievement Reviewed From Prior Knowledge - Fikri Aulia; Bilqis Nur Faizata; Wikan Budi Utami; M Shaefur Rokhman (IndoMath: Indonesia Mathematics Education, 2020)
This study aims to determine whether there are differences in mathematics learning achievement in students who use the Missouri Mathematics Project model and students who use the direct learning model in terms of initial abilities. The study population was conducted in class VII students of SMP Negeri 19 Tegal in the 2018/2019 school year. Sampling using cluster random sampling. Calculation of normality test, homogeneity, and one-way ANOVA test shows that the sample is normally distributed, homogeneous and has an equal sample. Before the hypothesis test, the hypothesis prerequisite test is normality and homogeneity. From the calculations, the samples are normally distributed and homogeneous. Testing continues using the RAK, from the statistical results, there are differences in mathematics learning achievement among students who are taught using the Missouri Mathematics Project model and students who use the direct learning model in terms of initial ability